SC411 treatment can enhance survival in a mouse model of sickle cell disease. (July 2020) - Wu, Celeste Y.C.; Lopez-Toledano, Miguel A.; Daak, Ahmed A.; Clemons, Garrett A.; Citadin, Cristiane T.; Sancilio, Frederick D.; Rabinowicz, Adrian L.; Minagar, Alireza; Neumann, Jake T.; Lee, Reggie H.C.; Lin, Hung Wen
Abstract: Sickle cell disease (SCD) is one of the most common inherited blood disorder among African Americans affecting 70, 000–100, 000 individuals in the United States. It is characterized by abnormal hemoglobin (HbS) which develops into severe hemolytic anemia and vaso-occlusive crisis. Therefore, patients with SCD suffer from a chronic state of inflammation, which is responsible for multiple organ damage, ischemic attacks, and premature death. Another major hallmark of SCD patients is the abnormally low levels of omega-3 fatty acids, especially docosahexaenoic acid (DHA) in their red blood cell membranes. Treatment with DHA can reduce red blood cell adhesion and enhance cerebral blood flow, thus, our main goal is to investigate the effect of SC411, which is a novel, highly purified DHA ethyl ester formulation with a proprietary delivery platform in SCD. Utilizing a transgenic mouse model of SCD (HbSS-Townes) and recurrent hypoxic challenges (10%O2, 0.5% CO2 and balance N2 for 3 h) to mimic ischemic-like conditions, our data suggest that SC411 can elevate blood DHA and eicosapentaenoic acid (EPA) levels after 8 weeks of treatment. SC411 can also decrease arachidonic acid (AA) and sickling of red blood cells. In addition, SC411-treated SCD mice showed presented with cerebral blood flow, alleviated neuroinflammation, and revived working memory which ultimately enhanced overall survival. In summary, this study suggests that treatment with SC411 improves cellular and functional outcomes in SCD mice. This finding may provide novel therapeutic opportunities in the treatment against ischemic injury elicited by SCD.